2013
DOI: 10.1038/ncomms3512
|View full text |Cite
|
Sign up to set email alerts
|

Super liquid-repellent gas membranes for carbon dioxide capture and heart–lung machines

Abstract: In a gas membrane, gas is transferred between a liquid and a gas through a microporous membrane. The main challenge is to achieve a high gas transfer while preventing wetting and clogging. With respect to the oxygenation of blood, haemocompatibility is also required. Here we coat macroporous meshes with a superamphiphobic—or liquid repellent—layer to meet this challenge. The superamphiphobic layer consists of a fractal-like network of fluorinated silicon oxide nanospheres; gas trapped between the nanospheres k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
77
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 29 publications
(36 reference statements)
1
77
0
4
Order By: Relevance
“…213 Omniphobic coatings furthermore provide the ability to delay or to prevent corrosion of metals such as copper, iron, or aluminum upon immersion into concentrated acids or bases due to the reduced or hindered contact of the corrosive media with the metal. 215 The fractal-like network of fluorinated silica particles could efficiently inhibit the adsorption of proteins even upon 24 h exposure. Paven et al reported on the modification of macroporous membranes with a super-omniphobic layer for a potential application in carbon dioxide capture and heart-lung machines.…”
Section: Chemical Shielding and Non-fouling Characteristicsmentioning
confidence: 99%
“…213 Omniphobic coatings furthermore provide the ability to delay or to prevent corrosion of metals such as copper, iron, or aluminum upon immersion into concentrated acids or bases due to the reduced or hindered contact of the corrosive media with the metal. 215 The fractal-like network of fluorinated silica particles could efficiently inhibit the adsorption of proteins even upon 24 h exposure. Paven et al reported on the modification of macroporous membranes with a super-omniphobic layer for a potential application in carbon dioxide capture and heart-lung machines.…”
Section: Chemical Shielding and Non-fouling Characteristicsmentioning
confidence: 99%
“…In addition to this bone particular example, more general comments on bio‐inert materials and their interactions with the body can be found in the literature …”
Section: Existing Types Of “Classical” Implanted Medical Devices Estamentioning
confidence: 99%
“…Super liquid-repellent surfaces, or so-called superhydrophobic or superamphiphobic surfaces gained much attention [1][2][3][4][5][6] due their potential applications, e.g., as self-cleaning coatings, [7] membranes for gas exchange, [8,9] or to suppress the formation of biofilms. [10] Liquid drops resting on these surfaces exhibit receding contact angles of more than ≈140° and easily roll-off at tilting angles lower than 10°.…”
Section: Introductionmentioning
confidence: 99%